Islam and Religious Expression in Malaysia - Azizuddin Mohd., Sani (ISEAS Publishing, 2020)
This book attempts to analyse the concept of religious expression vis-à-vis freedom of speech in Malaysia from the philosophical, political and theoretical perspectives. It begins by discussing the major sources of religious expression that are firmly rooted in the societal and religious beliefs, constitution and legislation of the country. It also examines multiple facets of the Islamization policy in the country and to what extent such policy affects the exercise of domestic religious expression. The problems and challenges of domestic religious expression, theoretically and practically, will also be examined including the issues of radicalization and terrorism. After a change of power from the Barisan Nasional (BN) to Pakatan Harapan (PH) in 2018, this book attempts to explain PH's approach in dealing with the issue of Islam and religious expression in Malaysia.